Genome‐wide association study of milk production traits in a crossbred dairy sheep population using three statistical models. (8th June 2020) - Li, H.; Wu, X.‐L.; Tait, R.G.; Bauck, S.; Thomas, D.L.; Murphy, T.W.; Rosa, G.J.M.
Summary: Milk production is one of the most important characteristics of dairy sheep, and the identification of genes affecting milk production traits is critical to understanding the genetics and improve milk production in future generations. Three statistical techniques, namely GWAS, ridge‐regression BLUP and BayesC π, were used to identify SNPs in significant association with three milk production traits (milk yield, fat yield and protein yield) in a crossbred dairy sheep population. The results suggested that chromosomes 1, 3, 4, 5, 7 and 11 were likely to harbor genes important to milk production because these chromosomes had the greatest top‐100‐SNP variance contributions on the three milk production traits. The GWAS analysis identified between 74 and 288 genome‐wide significant SNP ( P < 0.05) whereas the BayesC π model revealed between six and 63 SNPs, each with >95% posterior probability of inclusion as having a non‐zero association effect on at least one of the three milk production traits. Positional candidate genes for milk production in sheep were searched, based on the sheep genomic assembly OAR version 3.1, such as those which map position coincided with or was located within 0.1 Mbp of a genome‐wide suggestive or significant SNP. These identified SNPs and candidate genes supported some previous findings and also added new information about genetic markers for genetic improvement of lactation in dairy sheep, but keeping in mind that the majority of these positional candidate genes are not necessarily true causative loci for these traits and future validations are thus necessary.